VARIATIVITY OF CLINICAL-PSYCHOPATHOLOGICAL CONTENT OF DISORDERS RELATED TO ALCOHOL CONSUMPTION IN PERSONS WITH DIFFERENT PSYCHOLOGIC TRAUMATIC EXPERIENCES AND LEVELS OF PSYCHOSOCIAL STRESS - Gaponov, K.D. (Inter Collegas, 2019)
VARIATIVITY OF CLINICAL-PSYCHOPATHOLOGICAL CONTENT OF DISORDERS RELATED TO ALCOHOL CONSUMPTION IN PERSONS WITH DIFFERENT PSYCHOLOGIC TRAUMATIC EXPERIENCES AND LEVELS OF PSYCHOSOCIAL STRESSGaponov K.D.The article presents the results of a comprehensive survey of 312 men suffering from alcohol dependence: 107 combatants, 89 forcibly displaced persons and 116 civilians in the city of Kharkiv and Kharkiv region. The study has shown that the clinical diversity and severity of disorders associated with alcohol consumption (the style of alcohol consumption, the ability to control the attraction to consume, tolerance, the structure of the withdrawal state, etc.), and their psychopathological arrangement (depression, anxiety, interpersonal sensitivity, hostility, phobic anxiety, somatization, paranoia) are associated with the severity of psychosocial stress that the patients experience. The factor of the presence of psychotraumatic experience, not associated with a distinct response to a stressful event, does not significantly affect the variability of psychopathological symptoms of individuals with alcohol dependence. The revealed patterns should be taken into account when developing treatment and rehabilitation and preventive measures for persons suffering from alcohol dependence.Key words: psychosocial stress, psychotraumatic experience, psychopathological manifestations, disorders related to the alcohol consumption. ВАРІАТИВНІСТЬ КЛІНІКО-ПСИХОПАТОЛОГІЧНОГО ЗМІСТУ РОЗЛАДІВ, ПОВ’ЯЗАНИХ ІЗ ВЖИВАННЯМ АЛКОГОЛЮ, У ОСІБ З РІЗНИМ ПСИХОТРАВМАТИЧНИМ ДОСВІДОМ І РІВНЕМ ПСИХОСОЦІАЛЬНОГО СТРЕСУГапонов К.Д.На основі результатів комплексного обстеження 312 чоловіків, хворих на алкогольну залежність (АЗ): 107 комбатантів, 89 вимушено переміщених осіб та 116 осіб – цивільних мешканців м. Харкова і Харківської області, доведено, що клінічна різноманітність і вираженість розладів, пов’язаних із вживанням алкоголю (стиль вживання алкоголю, здатність контролю над потягом до вживання, толерантність, структура стану відміни та ін.), та їх психопатологічне аранжування (депресія, тривога, міжособистісна сенситивність, ворожість, фобічна тривожність, соматизація, паранояльність), асоційовані з вираженістю психосоціального стресу, що випробовують хворі. Фактор наявності психотравматичного досвіду, не асоційований із виразним реагуванням на стресову подію, не справляє суттєвого впливу на варіативність психопатологічної симптоматики осіб з АЗ. Виявлені закономірності повинні враховуватися при розробці лікувально-реабілітаційних та профілактичних заходів осіб, що страждають на АЗ.Ключові слова: психосоціальний стрес, психотравмуючий досвід, психопатологічні прояви, розлади, пов’язані із вживання алкоголю. ВАРИАТИВНОСТЬ КЛИНИКО-ПСИХОПАТОЛОГИЧЕСКОГО СОДЕРЖАНИЯ РАССТРОЙСТВ, СВЯЗАННЫХ С УПОТРЕБЛЕНИЕМ АЛКОГОЛЯ, У ЛИЦ С РАЗНЫМ ПСИХОТРАВМАТИЧЕСКИМ ОПЫТОМ И УРОВНЕМ ПСИХОСОЦИАЛЬНОГО СТРЕССАГапонов К.Д.На основе результатов комплексного обследования 312 мужчин, больных алкогольной зависимостью (АЗ): 107 комбатантов, 89 вынужденно перемещенных лиц и 116 жителей г. Харькова и Харьковской области, доказано, что клиническое разнообразие и выраженность расстройств, связанных с употреблением алкоголя (стиль употребления алкоголя, способность контроля над влечением к употреблению, толерантность, структура состояния отмены и др.) и их психопатологическая аранжировка (депрессия, тревога, межличностная сензитивность, враждебность, фобическая тревожность, соматизация, паранояльность), ассоциированы с выраженностью психосоциального стресса, испытываемым пациентами. Фактор наличия психотравматического опыта, не ассоциированный с выраженным реагированием на стрессовое событие, не оказывает существенного влияния на вариативность психопатологической симптоматики лиц с АЗ. Выявленные закономерности должны учитываться при разработке лечебно-реабилитационных и профилактических мероприятий для лиц, страдающих АЗ.Ключевые слова: психосоциальный стресс, психотравмирующий опыт, психопатологические проявления, расстройства, связанные с употреблением алкоголя.